Inflation Expectations and the Two Forms of Inattentiveness - Joshy Easaw; Roberto Golinelli (Cardiff University, Cardiff Business School, 2014)
The purpose of the present paper is to investigate the structure and dynamics of professionals' forecast of inflation. Recent papers have focused on their forecast errors and how they may be affected by informational rigidities, or inattentiveness. In this paper we extend the existing literature by considering a second form of inattentiveness. While showing that both types of inattentiveness are closely related, we focus on the inattentiveness that forecasters face when undertaking multi-period forecast and, thereby, the expected momentum of inflation. Using number survey-based data for the US and UK, we establish a new structure for the professional's forecast error with direct implications for the persistence of real effects
Keywords: E3; E4; E5; 330; Expectations; Information Rigidity; Survey Forecasts